Impact of construction on landscapes of the forest-step zone of Ukraine - S. P. Sonko; I. D. Zelenchuk (Людина і довкілля: Проблеми неоекології)
Purpose. Analysis of the impact of the construction of quickly assembled buildings with different frames on living and inert landscape components in the conditions of the Western part of the forest-steppe zone of Ukraine.